Study on hydrodynamic characteristics and influence factors of asphalt pavement runoff - Xiao, Wang (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
A hydrodynamic model is developed for rainfall-runoff on asphalt pavement using two-dimensional shallow water equations. A simple yet precise expression is presented to compute flow velocity in order to alleviate the problems associated with numerical instabilities due to small water depths of thin sheet flow. The developed model performed well against measured data and numerical results in two segments. Then, the model was applied to study the influence of highway horizontal alignment, drainage manner, rainfall pattern, surface roughness and geometric parameters on pavement runoff. The results demonstrate that: (i) the influence of highway horizontal alignment on pavement runoff is nonsignificant, while that of drainage manner and the pavement surface roughness is significant. Great differences are observed in flow depth under concentrated drainage and overflow drainage conditions, especially in the area beyond 6 m away from the highway center axis; (ii) remarkable differences in maximum flow depth and peak runoff are presented under uneven and even rainfall conditions, while no great differences are found under three uneven rainfall conditions (front type, center front type and back front type); (iii) the sensitivity of the geometric parameters to the maximum flow depth from strong to weak is cross slope, width, slope length, and longitudinal slope under overflow drainage condition; while that is width, slope length, longitudinal slope and cross slope under concentrated drainage condition